The influencing factors of CO2 emissions and the adoption of eco-innovation across G-7 economies: A novel hybrid mathematical and statistical approach - Rehman, Erum; Rehman, Shazia; Mumtaz, Ayesha; Jianglin, Zhang; Shahiman, Muhammad Ali (Frontiers in Environmental Science, 2022)
The present study empirically analyzes the role of eco-innovation in plummeting carbon dioxide (CO2) emissions in conjunction with renewable energy usage, foreign direct investment, and trade openness for the states in G-7 from 1990 to 2019 in a mathematical and statistical context. Under the dynamical framework, the estimates of mathematical grey relational analyses indicate that eco-innovation holds a stronger degree of association with CO2 emissions. Further, the estimates demonstrate that, compared to the other G-7 states, Japan is the country where eco-innovation is a more striking variable. However, renewable energy utilization seems weaker in Japan, which necessitates adopting renewable energy to curb carbon emissions in the region. Statistically, the odds ratio illustrates a similar pattern, demonstrating that the odds of occurrence for eco-innovation are much stronger in reducing the rising levels of carbon emissions within the G-7 states. Moreover, trade openness and foreign direct investment were revealed to be the leading contributors to carbon emissions in Germany and Canada, respectively, whilst appearing to be significant variables in lowering emissions in the United States and the United Kingdom. The outcomes of this investigation offer significant perspectives for policymakers in formulating holistic and environmentally friendly policies by embracing eco-innovation as a potentially significant component for sustainable economic expansion and environmental health.